Transposed Maxillary Canines: Narrative Review with Clinical Case Report - Teresa Pinho; Rui Amaral (Dentistry Journal)
Permanent maxillary canines are key teeth from both functional and aesthetic perspectives. Tooth transposition, a rare anomaly where two permanent teeth exchange positions within the same quadrant, poses significant diagnostic and therapeutic challenges. This study aimed to identify the clinical conditions guiding the decision to correct or maintain maxillary canine transposition through a narrative review of the literature, complemented by a detailed clinical case. Following PRISMA guidelines, a search of PubMed, ScienceDirect, Cochrane Library, EBSCO, and Scopus databases (2014–May 2024) yielded 19 relevant studies. This review found no consensus on treatment protocols, reinforcing the need for individualized decision-making based on patient characteristics, anatomical constraints, and clinician expertise. While orthodontic correction can yield favorable aesthetic outcomes, it requires meticulous planning and biomechanical control. Conservative approaches are often indicated in early-diagnosed or anatomically complex cases. The clinical case illustrates the complexity of managing the transposition, specifically of the maxillary canine into the central incisor position, emphasizing the importance of early diagnosis, digital planning, and a multidisciplinary approach for functional and aesthetic success.